The effect of respiratory augmented reality media on analysis and evaluation skills of eight grades students - Tri Jalmo; Ismi Rakhmawati; Kiki Nuraini (Biosfer: Jurnal Pendidikan Biologi, 2022)
The use of learning media on respiratory system material is needed so that the material presented can be understood thoroughly. One of the media that can be used to visualize the respiratory system material is Augmented Reality (AR). The purpose of this study was to determine the effect of using AR media on improving students' higher order thinking skills on the respiratory system material for class VIII at SMP Negeri 12 Bandar Lampung. The method used in this study is a quasi-experimental method with a non-equivalent pretest-posttest design. The sampling technique in this study used a purposive sampling technique. The research sample used was students of class VIII A as the experimental class and VIII C as the control class, with a total sample of 62 students. The data on the average value of pretest, posttest, and N-Gain as a result of the increase in students were analyzed by using the Independent Sample t-test. The results showed that the HOTS ability of students was in the medium category with N-gain in the experimental class of 0.58 ± 0.21 and the HOTS ability of students in the low category with N-gain in the control class was 0.29 ± 0.14. Statistical analysis with T-test showed that the use of AR media had a significant effect on increasing students' HOTS.